Analysis Marketing Strategy of Coffee Luwak Cikole; A Case Study - satim hamid; Pupung Purnamasari (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
This research is the result of a survey in the coffee Luwak Cikole Lembang Bandung production house that produces Luwak coffee from beans which are first eaten by mongoose animals. the purpose of this research is to deeply understand the process of implementing marketing and developing marketing strategies. The research method used is qualitative with field survey techniques. the results of the research show about the marketing process of Cikole Luwak coffee through several marketing processes including through product variables, price, promotion and distribution. The marketing process is carried out mostly through word of mouth and publications through social media sites such as WhatsApp, Facebook and other social media. problem analysis developed from observations using a SWOT analysis faced by CV. Kopi Luwak Cikole as a local business actor in the coffee industry